Sociodemographic and clinical characteristics of patients with diabetic foot ulcer - Pedras, Carla Susana Abreu (2016)
Introduction: Diabetic foot is one of the most serious complications of diabetes affecting about 150% of all diabetes patients, and it is the leading cause of nontraumatic lower limb amputations. This study presents a sociodemographic and clinical characterization of patients with diabetic foot ulcer indicated for amputation surgery.Methods: A cross-sectional study with 206 patients with type 2 diabetes and a diabetic foot ulcer indicated for amputation surgery. Patients were assessed on sociodemographic and clinical characteristics, pain intensity and pain interference, after answering the Brief Pain Inventory, and on pain descriptors according to the Douleur Neuropathique 4.Results: Most patients were male, with little formal education and a mean age of 66 years. They had been diagnosed with type 2 diabetes for 18 years in average, and diagnosed with diabetic foot ulcer in average 3 years prior to the assessment. About 59% of patients experienced pain in the lower limb that significantly interfered with all areas of their functioning.Conclusion: The social demographic variables play an important role in diabetic foot ulceration. Given that the neuropathic ulcers are more easily preventable, systematic monitoring of patients with neuropathy is important. In patients with neuroischemic foot, strategies to cope or manage more efficiently the pain are paramount. Intervention should be multidisciplinary and take into account sociodemographic and clinical factors, as well as the presence, intensity and interference of pain in the patient's daily life activities and whether the patient has family or caregiver support.